Macro-imbalances and bank lending: A case of Kenya's banking industry - Raphael Agung; Anthony Muli; David Ndwiga; Samantha Njoroge (Kenya Bankers Association (KBA), 2025)
The paper examines the effect of macroeconomic imbalances on bank lending with emphasis on the exchange rate movement, inflation differential and fiscal deficit. In the study, bank lending is modelled by gross loans and advances, assets quality and risk appetite. The panel GMM model results show that the Kenya shilling depreciation increased bank lending, improved asset quality and increases risk appetite. Inflationary pressures increased bank lending, worsens asset quality and leads to risk aversion. Lastly, fiscal deficit reduces bank lending, improves asset quality and increases risk appetite. This study's findings support bank behaviour during the study period- where the single obligor limits may not have been a consideration given low lending toward capital expenditure. The study found out that uncertainty with regard to policy makers' response to macro-imbalances impairs decision making by economic agents. Thus, it is important for policy makers to provide forward guidance on their possible action path. Additionally, the National Treasury needs to adhere to the fiscal path that it tables every fiscal year. Overall, commercial banks and other business enterprises require predictable guidance from the policy makers to aid in strategy formulation and balance sheet optimization decisions.
Keywords: 330; Economic situation; exchange rate; inflation; budget deficit; impact analysis; lending; bank; Kenya; Wirtschaftslage; Wechselkurs; Inflation; Haushaltsdefizit; Wirkungsanalyse; Kreditgeschäft; Bank; Kenia